(untitled) (Medico Legal Update, 2021)
Background: The aim of this study was to compare the anti-inflammatory effects of prednisolone and etoricoxib after third molar extraction. Method: A prospective, controlled study was conducted on 39 volunteers were allocated in three different groups, to receive either 120 mg etoricoxib or 10mg prednisolone 30 minutes prior to the procedure, and also a controlled group who didn’t receive any medication pre-operatively.Baseline measurements were obtained preoperatively, and subsequent assessments were made on immediate postoperative, at 48 hours and 7 days after surgery to measure postoperative facial swelling by use of linear measurements, interincisal mouth opening width and visual analog scale score for pain. The amount of analgesics consumed was recorded. Descriptive statistics were used to compare the two groups at P < 0.05. Conclusion: Considering the results that were obtained upon the efficacy of different pre-emptive medication, Etoricoxib showed statistically significant values in terms of pain reduction and restriction in mouth opening, in the other hand prednisolone showed significance results in terms of edema reduction.